2018
DOI: 10.18172/cig.3475
|View full text |Cite
|
Sign up to set email alerts
|

Catchment based hydrology under post farmland abandonment scenarios

Abstract: ABSTRACT. Vegetation expansion following farmland abandonment is a complex process that depends on multiple natural and human-induced factors, resulting in differences in the evolution of land cover on former cultivated fields, with various environmental implications. To assess the complexity of the hydrogeomorphological consequences of farmland abandonment, the Instituto Pirenaico de Ecología (CSIC) and the University of La P A P E R A C C E P T E D . P R E -P R I N T V E R S I O N

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 92 publications
0
15
0
2
Order By: Relevance
“…Organic farming has similar environmental impacts as land abandonment. From the water resources point of view, there is more water intercepted (catch crops, grass covers) and more water use by the plants such as Lana-Renault et al (2018) and Zuecco et al (2018) demonstrated at catchment scale, and Cerdà et al, (2018c) at plot scale. The benefits of organic farming are similar to the use of restoration strategies, such as Hueso-González et al (2017) found in fire-affected land with the use of compost and with the use of chipped pruned branches and straw mulches.…”
Section: The Benefits Of Organic Farmingmentioning
confidence: 99%
“…Organic farming has similar environmental impacts as land abandonment. From the water resources point of view, there is more water intercepted (catch crops, grass covers) and more water use by the plants such as Lana-Renault et al (2018) and Zuecco et al (2018) demonstrated at catchment scale, and Cerdà et al, (2018c) at plot scale. The benefits of organic farming are similar to the use of restoration strategies, such as Hueso-González et al (2017) found in fire-affected land with the use of compost and with the use of chipped pruned branches and straw mulches.…”
Section: The Benefits Of Organic Farmingmentioning
confidence: 99%
“…When the precipitation passing through the grassland quickly forms surface runoff and interflow, its causes more blue water flow [45]. The interception for the farmland is relatively high due to the planting density of the farmland, which can influence the hydrological processes of green and blue water flow [46].…”
Section: Discussionmentioning
confidence: 99%
“…El reto más importante de cara al futuro es decidir cómo se gestiona este paisaje abandonado y recolonizado por bosques y matorrales, aspecto en el que hay todavía mucha controversia (Conti & Fagarazzi, 2004;Cramer et al, 2007;Navarro & Pereira, 2012;Nogués et al, 2016;Lasanta et al, 2015Lasanta et al, , 2018Robledano Aymerich et al, 2016). El asunto es de gran transcendencia no solo porque afecta a la conservación de paisajes con gran valor cultural; también afecta a cuestiones tales como la biodiversidad (Lasanta Martínez et al, 2013b), el funcionamiento hidrológico de laderas y la generación de escorrentía (Beguería et al, 2003;Lana-Renault et al, 2018). Matorrales y bosque ocupan la mayor parte de los antiguos campos de cultivo, a veces incentivados por repoblaciones forestales que se escudaron en la necesidad de controlar la erosión y la generación de escorrentía en las áreas que habían sufrido mayor presión, es decir, el Prepirineo, las laderas meridionales del flysch en contacto con la Depresión Interior Altoaragonesa y las proximidades de los pueblos altopirenaicos.…”
Section: Los Cambios Recientes Y Sus Impactos: La Deconstrucción De Uunclassified